Study on the Influencing Factors of the Profitability of A-share Listed Catering Companies Based on DuPont Analysis - Dai, Ting (Pacific International Journal, 2023)
This study aims to determine the financial indicators that affect the profitability of Chinese A-share listed catering companies. The literature shows that more profitable companies are often more competitive and can also bring greater returns to investors. Therefore, it seems very necessary to identify the factors that affect the profitability of A-share listed catering companies. This study was based on the samples of the four catering companies,Tongqinglou,Guangzhou Restaurant ,Quanjude Group,Xi’an Catering,listed on China A-shares from 2018 to 2022. In order to determine the indicators affecting the profitability of the listed catering companies, based on DuPont analysis ,I conducted a large number of data analysis on the financial statements of these four companies and preliminarily determined 12 indicators. In order to determine the significance of the impact of each indicator on profitability, I used correlation analysis for screening.And finally, seven indicators were determined, namely: Return on equity, Return on total asset,Sales profit margin, Cost profit margin, Earnings per share , Total assets turnover ratio, and Profit rate on fixed assets.